Hard coating composition, hard coating film using same, window and image display device
By using a hard coat composition containing acrylic silane and fluorine UV curing functional groups, it is directly formed on the glass for display, solving the problem of complex production and insufficient adhesion in the prior art, and achieving a high-performance hard coat film and windows.
Patent Information
- Application Number
- CN202380050907.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-22
- Publication Date
- 2025-02-18
AI Technical Summary
The existing flexible display windows require multiple impact absorbing layers and adhesive layers during construction, resulting in complex production processes and lack of methods to directly form durable substrate layers, which affects adhesive force and mechanical properties.
A hard coat composition containing an acrylic silane compound and a fluorine-based UV curing functional group is used to form a hard coat film, which is directly in contact with the glass for the display, and the intermediate substrate layer is omitted, and the process is simplified.
It realizes the high transmittance, scratch resistance, stain resistance, wear resistance, reagent resistance, adhesion and bending resistance of hard coat film, and improves the equipment reliability of flexible displays.
Smart Images

Figure CN119487131A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hard coating composition, a hard coating film, a window and an image display device using the hard coating composition. Background Art
[0002] In recent years, image display devices such as liquid crystal display (LCD) devices and organic light emitting display (OLED) devices have continued to become thinner and more flexible. Such image display devices are widely used in various smart devices characterized by portability, such as smart phones, tablet PCs, and various wearable devices.
[0003] In such flexible displays, an additional substrate layer is sometimes provided on one or both sides of the thin glass as a window layer to provide durability such as hardness, bending properties, and mechanical properties such as antifouling properties while maintaining transparency.
[0004] Korean Patent Publication No. 10-2021-0150626 provides a window having improved impact resistance while maintaining foldable characteristics by including one or more impact absorbing layers and coating layers on a glass substrate.
[0005] However, when forming the above-mentioned window, an additional base material layer such as an adhesive layer is sandwiched in order to arrange a plurality of impact absorbing layers, which has caused a problem that the production process of the substrate becomes complicated.
[0006] Therefore, the actual situation is that it is necessary to develop a hard coating film, window and image display device that has durability suitable for achieving flexible characteristics by directly forming a base material layer that provides durability on glass to simplify the process, make it excellent in adhesion, be transparent, and make it excellent in mechanical properties such as bending characteristics and anti-fouling characteristics. Summary of the invention
[0007] Technical issues
[0008] In order to solve the above problems, an object of the present invention is to provide a hard coating composition having excellent quality and to provide a hard coating film formed from the hard coating composition.
[0009] Specifically, the purpose is to provide a window and an image display device that are excellent in transmittance, scratch resistance, surface pencil hardness, antifouling properties, abrasion resistance, chemical resistance, adhesion, high temperature and high humidity adhesion, bending resistance, and Vickers hardness of the hard coating layer by applying the above-mentioned hard coating film.
[0010] However, the problems to be solved by the present invention are not limited to the problems mentioned above, and a person skilled in the art should be able to understand other problems not mentioned based on the following description.
[0011] Solution to the problem
[0012] The present invention relates to a hard coating composition, which comprises an acrylic silane compound and a compound containing a fluorine-based UV curable functional group. The content of the acrylic silane compound is greater than 10% by weight relative to the total weight of the composition.
[0013] The present invention is characterized in that the hard coating layer formed by the hard coating composition has a Vickers hardness of 25 kgf / mm 2 above.
[0014] In the present invention, the fluorine-based UV-curable functional group-containing compound may have 1 to 6 UV-curable functional groups.
[0015] The present invention may further include one or more selected from the group consisting of a photopolymerizable compound, an initiator, and a solvent.
[0016] In the present invention, the photopolymerizable compound may include hexafunctional or higher-functional urethane (meth)acrylate.
[0017] In the present invention, the content of the hexafunctional or higher functional urethane (meth)acrylate may be greater than 10 parts by weight based on 100 parts by weight of the total photopolymerizable compound.
[0018] In the present invention, the photopolymerizable compound may further contain an inorganic nanofiller.
[0019] The present invention may also include additives.
[0020] In the present invention, the additive may include at least one selected from the group consisting of a leveling agent, a UV stabilizer, and a heat stabilizer.
[0021] Furthermore, the present invention relates to a hard coating film formed on a display glass and formed from the hard coating composition.
[0022] In the present invention, the display glass may be ultra-thin glass (Ultra Thin Glass, UTG).
[0023] The present invention is characterized in that the display glass and the hard coating layer can be formed in direct contact with each other without including any other layer.
[0024] The present invention can be applied to flexible displays.
[0025] Furthermore, the present invention may relate to a window including display glass and the hard coating film formed on the display glass.
[0026] Furthermore, the present invention may relate to an image display device including the above-mentioned window.
[0027] Effects of the Invention
[0028] The hard coating composition of the present invention, the hard coating film, the window and the image display device using the same have excellent physical properties such as transmittance, scratch resistance, pencil hardness, antifouling property, wear resistance, chemical resistance, adhesion, high temperature and high humidity adhesion and bending resistance, and Vickers hardness of the hard coating layer, thereby improving the reliability of the device when applied to a flexible display.
[0029] Furthermore, the hard coat film of the present invention does not include an additional substrate between the glass and the hard coat film, but is formed in direct contact with the glass and the hard coat film. Therefore, the step of bonding the substrate layers can be omitted, and the production process can be simplified compared with the related art. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The laminated structure of a glass laminate for displays on which a hard coating film is laminated according to one embodiment of the present invention is shown.
[0031] The meanings of the symbols in the above figure are as follows:
[0032] 100: Laminated body
[0033] 110: Display glass
[0034] 120: Hard coating DETAILED DESCRIPTION
[0035] The present invention relates to a hard coating composition for manufacturing a hard coating film suitable for a flexible display, a hard coating film comprising a hard coating layer manufactured thereby, a glass laminate for a display laminated with the hard coating film, and a window and an image display device using the same. The hard coating composition comprises an acrylic silane compound and a compound containing a fluorine-based UV-curable functional group, and the content of the acrylic silane compound is greater than 10% by weight relative to the total weight of the composition.
[0036] Hereinafter, preferred embodiments of the present invention will be described in detail. However, these embodiments are provided for the purpose of illustrating the present invention in more detail, and it is obvious to a person skilled in the art that the scope of the present invention is not limited by these embodiments.
[0037] The terms "comprises" and / or "comprising" used in this specification are used to mean that they do not exclude the existence or addition of one or more other constituent elements, steps, operations and / or elements other than the mentioned constituent elements, steps, operations and / or elements. Throughout the specification, the same reference numerals refer to the same constituent elements.
[0038] Figure 1 The structure of a laminate including a hard coating film produced from a hard coating composition according to one embodiment of the present invention is shown. Figure 1 As shown, the display glass laminate 100 of the present invention may have a structure including a display glass 110 and a hard coating film 120 formed on the display glass 110 .
[0039] <Hard Coating Composition>
[0040] The hard coating composition of one embodiment of the present invention is characterized in that it contains an acrylic silane compound and a compound containing a fluorine-based UV-curable functional group, and the content of the acrylic silane compound is greater than 10% by weight relative to the total weight of the composition.
[0041] In addition, the hard coating composition of one embodiment of the present invention may further include a photopolymerizable compound, a solvent and / or an initiator, and may further include one or more additives selected from the group consisting of a leveling agent, a UV stabilizer and a heat stabilizer, etc., as needed.
[0042] The hard coating composition of the present invention can be applied to glass, preferably ultra-thin glass, and can have excellent adhesion to display glass and improve mechanical properties such as transmittance, scratch resistance, pencil hardness, antifouling properties, abrasion resistance, chemical resistance, adhesion, high temperature and high humidity adhesion, bending resistance and / or Vickers hardness of the hard coating layer.
[0043] Acrylic silane compounds
[0044] The acrylic silane compound is a compound having a structure containing a monomer having four chemical groups bonded to a silicon (Si) element and a (meth)acryloyl group. The silyl group of the acrylic silane forms a chemical bond with the glass of the window laminate, and the acryl group forms a cross-linking bond with the UV curable hard coating composition, thereby imparting excellent high temperature and high humidity durability and having excellent durability.
[0045] Specifically, the acrylic silane compound of the present invention may have a structure of Chemical Formula 1 below.
[0046] [Chemical formula 1]
[0047]
[0048] In the above chemical formula 1, R1 may include any substituent having a double bond without limitation, for example, an alkenyl group or oxygen having 1 to 5 carbon atoms. R2 may each independently be an alkyl group having 1 to 5 carbon atoms. R3 may be hydrogen or methyl. From the perspective of achieving the effect of the present invention, c is more preferably an integer of 4 to 14.
[0049] According to one embodiment of the present invention, the content of the acrylic silane compound may be greater than 10% by weight, preferably greater than 11% by weight and less than 30% by weight, relative to the total weight of the hard coating composition. In particular, when the content of the acrylic silane compound is less than 10% by weight relative to the total weight of the hard coating composition, there is a problem that the reactivity between the glass of the window laminate and the acrylic silane compound is low and the high temperature and high humidity durability is poor.
[0050] Furthermore, by including the acrylic silane compound in the above range, the following advantages are achieved: the hard coating layer formed by the hard coating composition has good adhesion to the substrate, can provide flexibility to the film substrate layer and has the effect of preventing breakage during repeated folding, and can impart bending resistance.
[0051] Compounds containing fluorine-based UV-curable functional groups
[0052] The compound containing a fluorine-based UV-curable functional group is a component that imparts antifouling properties and abrasion resistance, and is not particularly limited as long as it contains fluorine and has a UV-curable functional group.
[0053] Specifically, acrylates, methacrylates, vinyls, etc. containing perfluorinated groups can be used. At this time, the compound containing a fluorinated UV-curable functional group preferably has 1 to 6 UV-curable functional groups, but the scope of the present invention is not limited thereto, and any substance having a UV-curable functional group and containing a fluorinated group can be used.
[0054] According to one embodiment of the present invention, the compound containing a fluorine-based UV curable functional group preferably contains 0.01 to 30% by weight, more preferably 0.5 to 10% by weight, relative to the total weight of the hard coating composition. If it is less than 0.01% by weight, it is difficult to fully achieve wear resistance and antifouling properties. When it is greater than 30% by weight, the film hardness and wear resistance may even be reduced.
[0055] Photopolymerizable compounds
[0056] The photopolymerizable compound used for forming the hard coat layer of the present invention is a compound containing a photopolymerizable functional group, and may be a photopolymerizable monomer, a photopolymerizable oligomer, or the like, and may be, for example, a photoradical polymerizable compound.
[0057] The photopolymerizable monomers may be any monomers used in the art that have unsaturated groups such as (meth)acryloyl, vinyl, styryl, and allyl groups in the molecule as photocurable functional groups. More specifically, for example, monofunctional and / or multifunctional (meth)acrylates may be used alone or in combination of two or more.
[0058] In the present invention, "(meth)acryloyl-" means "methacryloyl-", "acryloyl-" or both.
[0059] Specific examples of the (meth)acrylate monomer include: (meth)acrylates such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerol tri(meth)acrylate, tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol (meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, bis(2-hydroxyethyl)isocyanurate di(meth)acrylate, and poly(meth)acrylates obtained by adding ethylene oxide or propylene oxide to the above (meth)acrylates; Oligomeric ester (meth)acrylates, oligomeric ether (meth)acrylates, oligomeric urethane (meth)acrylates and oligomeric epoxy (meth)acrylates having 1 to 3 (meth)acryloyl groups in the (meth)acrylate; hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate and products obtained by adding ethylene oxide or propylene oxide to the above (meth)acrylates; and monomers having trifunctional or less (meth)acryloyl groups such as mono(meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, stearyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate and phenoxyethyl (meth)acrylate; and dipentaerythritol hexa(meth)acrylate, dipentaerythritol hydroxypenta(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate and the like. These can be used alone or in combination of two or more.
[0060] The photopolymerizable oligomer may be, for example, one or more selected from the group consisting of epoxy (meth)acrylate, urethane (meth)acrylate, and polyester (meth)acrylate. Specifically, urethane (meth)acrylate and polyester (meth)acrylate may be mixed for use, or two polyester (meth)acrylates may be mixed for use. In order to improve the scratch resistance and hardness of the cured product and increase the elastic modulus of the hard coating, it is preferred to include a urethane (meth)acrylate oligomer.
[0061] The urethane (meth)acrylate can be produced by reacting a polyfunctional (meth)acrylate having a hydroxyl group in the molecule with a compound having an isocyanate group in the presence of a catalyst according to a method known in the art.
[0062] Specific examples of the multifunctional (meth)acrylate having a hydroxyl group in the molecule may be one or more selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxyisopropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, caprolactone ring-opening hydroxy acrylate, a pentaerythritol tri / tetra(meth)acrylate mixture, and a dipentaerythritol penta / hexa(meth)acrylate mixture.
[0063] Specific examples of the compound having an isocyanate group include a compound selected from the group consisting of 1,4-diisocyanatobutane, 1,6-diisocyanatohexane, 1,8-diisocyanatooctane, 1,12-diisocyanatododecane, 1,5-diisocyanato-2-methylpentane, trimethyl-1,6-diisocyanatohexane, 1,3-bis(isocyanatomethyl)cyclohexane, trans-1,4-cyclohexene diisocyanate, 4,4′-methylenebis(cyclohexyl isocyanate), isocyanate, and isocyanate. One or more selected from the group consisting of phorone diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, xylene-1,4-diisocyanate, tetramethylxylene-1,3-diisocyanate, 1-chloromethyl-2,4-diisocyanate, 4,4'-methylenebis(2,6-dimethylphenylisocyanate), 4,4'-oxybis(phenylisocyanate), trifunctional isocyanates of hexamethylene diisocyanate, and trimethylene propanol-added toluene diisocyanate.
[0064] More specifically, the urethane (meth)acrylate oligomer may be a compound including two or more substituents represented by the following Chemical Formula 2 and a (meth)acryloyl group, respectively, in a molecule.
[0065] [Chemical formula 2]
[0066] *-OC(=O)NH-*
[0067] The urethane (meth)acrylate oligomer can be obtained by reacting preferably 1 mol of a diisocyanate represented by the following Chemical Formula 3 with preferably 2 mol of an active hydrogen-containing polymerizable unsaturated compound.
[0068] [Chemical formula 3]
[0069] R4-OC(=O)NH-R6-NHC(=O)O-R5
[0070] In the formula, R4 and R5 are each independently a (meth)acryloyl-containing substituent derived from an active hydrogen-containing polymerizable unsaturated compound, and R6 is a divalent substituent derived from a diisocyanate.
[0071] Specific examples of the urethane (meth)acrylate oligomer include products obtained by the reaction of 2-hydroxyethyl (meth)acrylate and 2,4-toluene diisocyanate, the reaction of 2-hydroxyethyl (meth)acrylate and isophorone diisocyanate, the reaction of 2-hydroxybutyl (meth)acrylate and 2,4-toluene diisocyanate, the reaction of 2-hydroxybutyl (meth)acrylate and isophorone diisocyanate, the reaction of pentaerythritol tri(meth)acrylate and 2,4-toluene diisocyanate, the reaction of pentaerythritol tri(meth)acrylate and isophorone diisocyanate, the reaction of pentaerythritol tri(meth)acrylate and dicyclohexylmethane diisocyanate, the reaction of dipentaerythritol penta(meth)acrylate and isophorone diisocyanate, and the reaction of dipentaerythritol penta(meth)acrylate and dicyclohexylmethane diisocyanate.
[0072] Polyester (meth)acrylate can be produced by reacting polyester polyol with acrylic acid according to a method known in the art.
[0073] The polyester (meth)acrylate may be, for example, one or more selected from the group consisting of polyester acrylate, polyester diacrylate, polyester tetraacrylate, polyester hexaacrylate, polyester pentaerythritol triacrylate, polyester pentaerythritol tetraacrylate, and polyester pentaerythritol hexaacrylate, but is not limited thereto.
[0074] In particular, in order to ensure high Vickers hardness, hexafunctional or higher polyfunctional urethane (meth) acrylates having urethane groups capable of forming hydrogen bonds and capable of increasing the degree of crosslinking and / or tetradecafunctional polyester (meth) acrylates may be included. Although the tetradecafunctional polyester (meth) acrylate is a polyfunctional compound, it has the characteristic of reducing hardness when added to the composition due to its unique structure.
[0075] When two or more acrylates are mixed and used including hexafunctional or higher polyfunctional urethane (meth)acrylate, the content of the hexafunctional or higher polyfunctional urethane (meth)acrylate may be greater than 10 parts by weight relative to a total of 100 parts by weight of the photopolymerizable compound. In view of being able to increase the hardness of the hard coat film, it is more preferably greater than 10 parts by weight and less than 85 parts by weight.
[0076] The photopolymerizable monomer and the photopolymerizable oligomer may be used alone or in combination. When the photopolymerizable monomer and the photopolymerizable oligomer are used in combination, the handling properties and compatibility of the hard coating composition can be improved.
[0077] The content ratio of the photopolymerizable monomer to the photopolymerizable oligomer is not particularly limited, and can be appropriately selected in consideration of the storage modulus, shrinkage force, and operability of the hard coat layer, for example, the content ratio of the polymerizable oligomer to the polymerizable monomer can be a ratio of (1:10) to (10:1). When the content ratio of the polymerizable oligomer to the polymerizable monomer deviates from the above range, the storage modulus of the hard coat layer decreases or the shrinkage force increases, while the hardness and flexibility decrease, and curling may occur.
[0078] The content of the photopolymerizable compound is not particularly limited, and for example, the content may be 1 to 80% by weight, preferably 5 to 50% by weight, relative to the total weight of the hard coating composition. If the content of the photopolymerizable compound is less than 1% by weight, the elastic modulus of the hard coating layer decreases and cracks may easily occur in the hard coating layer when bent, and if the content is greater than 80% by weight, the viscosity increases and the coating property deteriorates, and the surface leveling may be insufficient, causing problems in appearance characteristics.
[0079] The above-mentioned photopolymerizable compound can be used together with an inorganic nanofiller to improve hardness and scratch resistance. The above-mentioned inorganic nanofiller can generally use an inorganic nanofiller of less than 100 nm, preferably 10 to 100 nm, and more preferably 10 to 50 nm. As a representative inorganic nanofiller, for example, silicon dioxide, aluminum oxide particles, titanium oxide particles and / or zinc oxide particles can be used, and silicon dioxide can be preferably used. The surface of silicon dioxide may or may not have a photocurable group that can participate in the photoreaction.
[0080] The inorganic nanofiller may be added by appropriately adjusting the content within a range that does not impair the effects of the present invention.
[0081] Solvents
[0082] The solvent is a substance capable of dissolving or dispersing the above-mentioned components, and any solvent known as a solvent for a coating layer-forming composition in the art can be used without limitation.
[0083] As the solvent that can be used, preferably alcohols (methanol, ethanol, isopropanol, butanol, methyl cellosolve, ethyl cellosolve, etc.), ketones (methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, dipropyl ketone, cyclohexanone, etc.), acetates (ethyl acetate, propyl acetate, n-butyl acetate, tert-butyl acetate, methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, methoxybutyl acetate, methoxypentyl acetate, etc.), hexanes (hexane, heptane, octane, etc.), benzenes (benzene, toluene, xylene, etc.), ethers (diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, propylene glycol monomethyl ether, etc.), etc. can be used. The above-exemplified solvents can be used alone or in combination of two or more.
[0084] According to one embodiment of the present invention, the solvent is used in an amount of 10 to 95 wt % relative to the total weight of the hard coating composition. If the content of the solvent is lower than the above content, the viscosity is high and the operability is poor. In addition, the swelling of the substrate film may not be fully performed. On the contrary, if the content is higher than the above range, the drying process takes a long time and the economic efficiency is poor. Therefore, it is appropriately used within the above range.
[0085] Initiator
[0086] The above-mentioned initiator can be used without limitation as long as it is an initiator used in the technical field. For example, one or more selected from the group consisting of hydroxyketones, aminoketones, hydrogen abstraction type photoinitiators and combinations thereof can be used.
[0087] Specifically, as the above-mentioned photoinitiator, one or more selected from the group consisting of 2-methyl-1-[4-(methylthio)phenyl]2-morpholinoacetone-1, diphenyl ketone, benzyl dimethyl ketal, 2-hydroxy-2-methyl-1-phenyl-1-ketone, 4-hydroxycyclophenyl ketone, 2,2-dimethoxy-2-phenyl-acetophenone, anthraquinone, fluorene, triphenylamine, carbazole, 3-methylacetophenone, 4-chloroacetophenone, 4,4-dimethoxyacetophenone, 4,4-diaminobenzophenone, 1-hydroxycyclohexyl phenyl ketone, benzophenone, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide and combinations thereof can be used.
[0088] Such a photoinitiator is used in an amount of 0.1 to 10% by weight, preferably 1 to 5% by weight, relative to the total weight of the hard coating composition. If the content is below the above range, the curing speed of the composition may be slow and the composition may not be cured, resulting in poor mechanical properties. On the contrary, if the content is above the above range, cracks may be generated in the coating film due to excessive curing.
[0089] additive
[0090] Furthermore, the hard coating composition used for forming the hard coating layer of the present invention may further contain additives such as a leveling agent, a UV stabilizer, and / or a heat stabilizer.
[0091] The leveling agent is a component that imparts smoothness and coating properties to the coating film. The leveling agent may be a leveling agent commonly used in the art, for example, a silicone leveling agent, a fluorine leveling agent, an acrylic polymer leveling agent, etc. These may be used alone or in combination of two or more, but are not necessarily limited thereto.
[0092] The content of the leveling agent may be 0.1 to 1 wt % relative to the total weight of the hard coating composition, but is not limited thereto.
[0093] UV stabilizers are components that block or absorb UV rays and prevent the cured hard coating from decomposing, changing color, or breaking due to exposure to UV rays. The above-mentioned UV stabilizers can be absorbers, quenchers, hindered amine light stabilizers (HALS, Hindered Amine Light Stabilizer), etc., which are classified according to the mechanism of action; or phenyl salicylate (Phenyl Salicylates, absorbers), benzophenone (Benzophenone, absorbers), benzotriazole (Benzotriazole, absorbers), nickel derivatives (quenchers), free radical scavengers (Radical Scavengers); etc., which are classified according to the chemical structure. They can be used alone or in combination of two or more, and their types are not particularly limited, as long as they are UV stabilizers that do not significantly change the initial color of the hard coating.
[0094] As the heat stabilizer, for example, polyphenols as primary heat stabilizers, phosphate esters and lactones as secondary heat stabilizers, which are commercially available products, can be used alone or in combination.
[0095] The above-mentioned ultraviolet stabilizer and heat stabilizer can be used in an appropriately adjusted content at a level that does not affect ultraviolet curability. Specifically, the content thereof is preferably 0.0 to 3 wt % relative to the total weight of the hard coating composition of the present invention.
[0096] The above-mentioned additives can be added by appropriately adjusting the content within a range that does not impair the effects of the present invention.
[0097] The hard coating layer can be produced by a method known in the art. The thickness of the hard coating layer is not particularly limited, and may be, for example, 5 to 100 μm. If the thickness is within the above range, more excellent hardness can be exhibited.
[0098] The hard coating film of the embodiment of the present invention may include a hard coating film 120 formed by coating a hard coating composition on a display glass 110 and performing drying and UV curing steps.
[0099] The step of drying the hard coating film may be performed using a heating tool such as a hot plate, a hot air circulation oven, an infrared oven, etc., and may be performed at a temperature of 50 to 150°C or 50 to 100°C.
[0100] In the step of curing the hard coating film, 50 to 1000 mJ / cm 2 , preferably 200 to 800 mJ / cm 2 As the light source used in the irradiation, a low-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, an argon laser, etc. can be used, and X-rays, electron beams, etc. can also be used as needed.
[0101] <Hard Coat 120>
[0102] The hard coating film 120 of the present invention is not particularly limited as long as it is produced from the above-mentioned hard coating composition.
[0103] According to one embodiment of the present invention, the hard coating film 120 is characterized in that it is formed by a hard coating composition containing an acrylic silane compound and a compound containing a fluorine-based UV-curable functional group, and the content of the acrylic silane compound is greater than 10 weight % relative to the total weight of the composition.
[0104] Reference Figure 1 The hard coating film 120 may be formed on the display glass 110 and may be formed on the outermost layer of the laminate 100. The hard coating film 120 is formed directly on the glass without another substrate layer such as an adhesive layer to ensure adhesion between substrates, and is exposed on the surface to impart impact resistance and antifouling properties to protect the film.
[0105] <Laminate for display>
[0106] The glass laminate 100 for display of the present invention is not particularly limited as long as it includes the hard coating film. Figure 1 As shown, the structure may include a display glass 110 and a hard coating film 120 formed on the display glass 110 .
[0107] Display glass 110
[0108] The display glass 110 is intended to replace the conventional glass substrate to support the hard coating layer 120 and other substrates or panels, and can be made of thin glass or curved glass for the display of electronic devices. The thin glass can include flat glass and flexible glass.
[0109] According to one embodiment of the present invention, the display glass 110 may be ultra-thin glass (UTG). Ultra-thin glass (UTG) is a component of ultra-thin tempered glass material used for display outer cover windows. It is an ultra-thin glass with high transparency and a thickness of about 10 to 100 μm, and has the characteristic of being flexible and foldable.
[0110] In the present invention, the above-mentioned "transparent" means that the transmittance of visible light is 70% or more or 80% or more.
[0111] The display glass 110 may include an additional substrate layer such as the hard coating film 120 to ensure durability. Generally, an adhesive layer or a sticking layer is included to form or bond the substrate layer, but the hard coating film according to the present invention is formed in direct contact with the display glass without including an additional substrate layer for bonding the hard coating layer, thereby simplifying the production process compared with conventional laminates.
[0112] <Window and Image Display Device>
[0113] Embodiments of the present invention provide a window and an image display device including the hard coating film 120 or a laminate 100 including the hard coating film 120 .
[0114] For example, the hard coating film or a laminate containing the hard coating film may be used as a window or a window laminate. In this case, at least one of a polarizing layer or a touch sensor layer may be laminated on one side of the window formed with the hard coating film. Such a window or a window laminate may be used as a window film formed on the outermost surface of an image display device. In addition, the hard coating film may also be inserted into the interior of an image display device, for example.
[0115] The above-mentioned image display device includes various image display devices such as liquid crystal display device, electroluminescent display device, plasma display device, field emission display device, etc., and can be a flexible display device with flexibility and bending characteristics.
[0116] In this case, the hard coating stack of the embodiment of the present invention can be more effectively used as the window or window stack of the above-mentioned flexible display device. Through the interaction between the substrate layer and the easy-adhesion layer contained in the hard coating film of the embodiment of the present invention, the flexibility and durability of the window can be improved at the same time, and the antistatic performance can also be achieved together. Thus, for example, the impact resistance and wear resistance of the above-mentioned flexible display device can be improved, and damage such as cracks and peeling can also be prevented when bending or folding (bending).
[0117] Implementation
[0118] The following are specific examples of the present invention. However, the present invention is not limited to the following examples, and can be implemented in various different ways. The examples are provided only to make the disclosure of the present invention complete and to fully inform the general technicians of the technical field to which the present invention belongs of the scope of the invention. The present invention is defined only by the scope of the claims. Unless otherwise stated, "%" and "parts" are mass % and mass parts, respectively.
[0119] Production Example: Production of Hard Coat Composition
[0120] Production Example 1
[0121] Relative to the total weight of the composition, 23.1 wt% of tetradecafunctional acrylate (Osaka Organic Chemical, VISCOAT#1000), 9.9 wt% of hexafunctional urethane acrylate (Kyoeisha, UA-306H), 1 wt% of 1-hydroxycyclohexyl phenyl ketone, 1 wt% of a fluorine-containing UV-curable functional group compound (Shin-Etsu Co., Ltd., KY-1203), 50 wt% of methyl ethyl ketone, and 15 wt% of an acrylic silane compound (Shin-Etsu Silicone, KR-513) were mixed using a stirrer and then filtered using a PP filter to prepare a hard coating composition.
[0122] Production Example 2
[0123] Relative to the total weight of the composition, 23.1 wt% of tetradecafunctional acrylate (Osaka Organic Chemical, VISCOAT#1000), 9.9 wt% of hexafunctional urethane acrylate (Kyoeisha, UA-306H), 1 wt% of 1-hydroxycyclohexyl phenyl ketone, 1 wt% of a fluorine-containing UV-curable functional group compound (Shin-Etsu Co., Ltd., KY-1203), 50 wt% of methyl ethyl ketone, and 15 wt% of an acrylic silane compound (Shin-Etsu Silicone, KBM-5803) were mixed using a stirrer and then filtered using a PP filter to prepare a hard coating composition.
[0124] Production Example 3
[0125] 9.9 wt % of tetradecafunctional acrylate (Osaka Organic Chemical, VISCOAT #1000), 23.1 wt % of hexafunctional urethane acrylate (Kyoei Co., Ltd., UA-306H), 1 wt % of 1-hydroxycyclohexyl phenyl ketone, 1 wt % of a fluorine-containing UV-curable functional group compound (Shin-Etsu Co., Ltd., KY-1203), 50 wt % of methyl ethyl ketone, and 15 wt % of an acrylic silane compound (Shin-Etsu Silicone, KR-513) were mixed with a stirrer relative to the total weight of the composition, and then filtered with a PP filter to prepare a hard coating composition.
[0126] Production Example 4
[0127] 9.9 wt % of tetradecafunctional acrylate (Osaka Organic Chemical, VISCOAT#1000), 23.1 wt % of hexafunctional urethane acrylate (Kyoei Co., Ltd., UA-306H), 1 wt % of 1-hydroxycyclohexyl phenyl ketone, 1 wt % of a fluorine-containing UV-curable functional group compound (Shin-Etsu Co., Ltd., KY-1203), 50 wt % of methyl ethyl ketone, and 15 wt % of an acrylic silane compound (Shin-Etsu Silicone, KBM-5803) were mixed with a stirrer relative to the total weight of the composition, and then filtered with a PP filter to prepare a hard coating composition.
[0128] Production Example 5
[0129] Relative to the total weight of the composition, 31.5 wt% of tetradecafunctional acrylate (Osaka Organic Chemical, VISCOAT #1000), 13.5 wt% of hexafunctional urethane acrylate (Kyoei Sha, UA-306H), 1 wt% of 1-hydroxycyclohexyl phenyl ketone, 1 wt% of a fluorine-containing UV-curable functional group compound (Shin-Etsu Co., Ltd., KY-1203), 50 wt% of methyl ethyl ketone, and 3 wt% of an acrylic silane compound (Shin-Etsu Silicone, KR-513) were mixed using a stirrer and then filtered using a PP filter to prepare a hard coating composition.
[0130] Production Example 6
[0131] Relative to the total weight of the composition, 31.5 wt% of tetradecafunctional acrylate (Osaka Organic Chemical, VISCOAT#1000), 13.5 wt% of hexafunctional urethane acrylate (Kyoei Sha, UA-306H), 1 wt% of 1-hydroxycyclohexyl phenyl ketone, 1 wt% of a fluorine-containing UV-curable functional group compound (Shin-Etsu Co., Ltd., KY-1203), 50 wt% of methyl ethyl ketone, and 3 wt% of an acrylic silane compound (Shin-Etsu Silicone, KBM-5803) were mixed using a stirrer and then filtered using a PP filter to prepare a hard coating composition.
[0132] Production Example 7
[0133] 13.5 wt% of tetradecafunctional acrylate (Osaka Organic Chemical, VISCOAT#1000), 31.5 wt% of hexafunctional urethane acrylate (Kyoeisha, UA-306H), 1 wt% of 1-hydroxycyclohexyl phenyl ketone, 1 wt% of a fluorine-containing UV-curable functional group compound (Shin-Etsu Co., Ltd., KY-1203), 50 wt% of methyl ethyl ketone, and 3 wt% of an acrylic silane compound (Shin-Etsu Silicone, KR-513) were mixed with a stirrer relative to the total weight of the composition, and then filtered with a PP filter to prepare a hard coating composition.
[0134] Examples and Comparative Examples: Preparation of Hard Coat Films
[0135] The hard coating compositions of the above-mentioned manufacturing examples 1 to 7 were stacked on the display glass according to the structure described in the following Table 1 to produce a hard coating film. Specifically, in order to form a hard coating layer, the composition of the manufacturing example corresponding to each embodiment and comparative example was applied on a 50 μm thin glass to form a hard coating layer. For the composition of each manufacturing example, the hard coating composition was applied 12 times using a rod coater, and the solvent was dried at 90°C for 2 minutes. Nitrogen was purged through the dried coating film, and the coating film was heated at 600 mJ / cm under nitrogen conditions. 2 The hard coating layer was formed to a thickness of 7 μm by irradiating UV light with a light intensity of 100 μm, thereby producing a final laminated hard coating film.
[0136] [Table 1]
[0137]
[0138]
[0139] -Tetradecafunctional polyester acrylate: VISCOAT#1000 (Osaka Organic Chemical)
[0140] - Hexafunctional urethane acrylate: UA-306H (Kyoeisha)
[0141] -Initiator: Micure CP4 (1-hydroxycyclohexyl phenyl ketone; Micure Specialty Chemicals, Inc.)
[0142] -Solvent: MEK (methyl ethyl ketone; Daelim Corporation)
[0143] - Fluorine-containing UV-curable functional group compound: KY-1203 (Shin-Etsu Co., Ltd.)
[0144] -Acrylic silane compound 1: KR-513 (Shin-Etsu Silicone Co., Ltd.)
[0145] -Acrylic silane compound 2: KBM-5803 (Shin-Etsu Silicone Co., Ltd.)
[0146] Experimental example
[0147] The physical properties of the hard coating films produced in Examples 1 to 4 and Comparative Examples 1 to 3 were measured by the following methods. The results are shown in Table 2 below.
[0148] (1) Transmittance
[0149] The transmittance of the coating film was measured using a haze meter HM-150N manufactured by Murakami Co., Ltd.
[0150] (2) Scratch resistance
[0151] After the substrate film and the glass were bonded together with a transparent adhesive with the hard coating facing upward, steel wool (#0000) was used to rub the glass at a speed of 500 g / cm 2 The scratch resistance was measured by reciprocating rubbing 10 times with a load of 1.50 g.
[0152] <Evaluation Criteria>
[0153] ○: When the measurement portion was observed by transmission and reflection using a three-wavelength lamp, no scratches were observed or 10 or less scratches were observed.
[0154] X: When the measurement portion is observed by transmission and reflection using a three-wavelength lamp, more than 10 scratches are observed.
[0155] (3) Pencil hardness
[0156] After fixing the substrate film to the glass with the hard coating facing upward, the pencil hardness was measured under a load of 1 kg. The test was performed 5 times with a pencil of the same hardness at a length of 1 cm, and the hardness that passed 4 or more times was marked as the pencil hardness.
[0157] (4) Antifouling
[0158] The contact angle of water was measured using a contact angle meter DSA100 from KRUSS. The droplet volume was set to 3 μl at room temperature. A water contact angle of 110° or more was considered a pass standard for the contact angle.
[0159] (5) Wear resistance
[0160] The test was conducted using a wear tester from Dacheng Precision Co., Ltd. The contact angle was measured after the coating surface was wiped 3,000 times with a wear test eraser and a 500g weight. At this time, a water contact angle of 95° or more was considered acceptable for wear resistance.
[0161] (6) Reagent resistance
[0162] The test was carried out by the wear test equipment of Dacheng Precision Co., Ltd. The contact angle was measured after wiping the coating surface 3000 times with a wear test eraser and a 500g weight. Ethanol (purity 99.8%) was applied to the wiped sample every 50 times. At this time, the water contact angle of 95° or more was defined as the qualified standard for chemical resistance.
[0163] (7) Adhesion
[0164] After the base film and glass were bonded with a transparent adhesive with the hard coating facing upward, 100 squares were cut horizontally and vertically at 1 mm intervals on the hard coating surface with a cutter, and then the adhesion test was performed three times with Mickybond tape.
[0165] The results are expressed as "the number of quadrilaterals that passed the tightness test / 100".
[0166] <Evaluation Criteria>
[0167] ○:100 / 100
[0168] X: 0 to 99 / 100
[0169] (8) High temperature and high humidity adhesion
[0170] After being placed in a constant temperature and humidity chamber at 60°C for 240 hours, the substrate film was bonded to the glass using a transparent adhesive with the hard coating facing upward. Then, 100 squares were cut horizontally and vertically at 1 mm intervals on the hard coating surface using a cutter, and then the adhesion test was performed three times using Mickybond tape.
[0171] The results are expressed as "the number of quadrilaterals that passed the tightness test / 100".
[0172] <Evaluation Criteria>
[0173] ○:100 / 100
[0174] X: 0 to 99 / 100
[0175] (9) Bending resistance
[0176] The hard coating film produced as described above was placed so that the hard coating layers were in contact with each other, and was repeatedly folded 200,000 times so that the curvature radius of the folded portion would be 5 mm to perform a test.
[0177] <Evaluation Criteria>
[0178] ○: No cracks or breaks
[0179] X: Cracks or breaks
[0180] (10) Vickers hardness test
[0181] The sample was placed so that the hard coating film faced upward, and the Vickers hardness of the hard coating layer was measured using a nano indenter (Fisher) at a micro load of 5 mN.
[0182] [Table 2]
[0183]
[0184] Referring to the experimental data in Table 1 above, in the case of Examples 1 to 4 to which the laminate of the present invention is applied, excellent results are shown in the evaluation of transmittance, scratch resistance, pencil hardness, antifouling, wear resistance, chemical resistance, adhesion, high temperature and high humidity adhesion, bending resistance, and Vickers hardness of the hard coating layer. On the other hand, Comparative Examples 1 to 3, which are deviated from the compositions of the embodiments of the present invention, do not conform to the present invention in one or more of the evaluation criteria for the evaluation of transmittance, scratch resistance, pencil hardness, antifouling, wear resistance, chemical resistance, adhesion, high temperature and high humidity adhesion, bending resistance, and Vickers hardness of the hard coating layer, and do not show physical properties suitable for flexible display applications. In particular, in the case of the comparative example in which the content of the acrylic silane compound is 10% by weight or less relative to the total weight of the hard coating composition, it can be confirmed that the adhesion under high temperature and high humidity conditions is significantly deteriorated.
[0185] Therefore, it was confirmed that the hard coating composition of the present invention, and the hard coating film, window, and image display device using the same have excellent physical properties in terms of durability, especially under high temperature and high humidity conditions.
[0186] Industrial Applicability
[0187] The hard coating composition of the present invention, the hard coating film, the window and the image display device using the same have excellent physical properties such as transmittance, scratch resistance, pencil hardness, antifouling property, wear resistance, chemical resistance, adhesion, high temperature and high humidity adhesion and bending resistance, and Vickers hardness of the hard coating layer, thereby improving the reliability of the device when applied to a flexible display.
Claims
1. A hard coating composition comprising an acrylic silane compound and a compound containing a fluorine-based UV-curable functional group, The content of the acrylic silane compound is greater than 10 wt % relative to the total weight of the composition.
2. A hard coating composition, characterized in that The Vickers hardness of the hard coating layer formed by the hard coating composition is 25 kgf / mm 2 above. 3 . The hard coating composition according to claim 1 , wherein the compound containing a fluorine-based UV-curable functional group has 1 to 6 UV-curable functional groups. 4 . The hard coating composition according to claim 1 , further comprising one or more selected from the group consisting of a photopolymerizable compound, an initiator, and a solvent.
5. The hard coating composition according to claim 4, characterized in that The photopolymerizable compound includes hexafunctional or higher-functional urethane (meth)acrylate. 6 . The hard coating composition according to claim 5 , wherein the content of the hexafunctional or higher functional urethane (meth)acrylate is greater than 10 parts by weight based on 100 parts by weight of the total photopolymerizable compound. 7 . The hard coating composition according to claim 4 , wherein the photopolymerizable compound further comprises an inorganic nanofiller.
8. The hard coating composition according to claim 1, further comprising an additive. 9 . The hard coating composition according to claim 8 , wherein the additive comprises at least one selected from the group consisting of a leveling agent, a UV stabilizer, and a heat stabilizer. 10 . A hard coating film formed on a display glass and formed from the hard coating composition according to claim 1 .
11. The hard coating film according to claim 10, characterized in that: The display glass is ultra-thin glass UTG.
12. The hard coating film according to claim 10, characterized in that: The display glass and the hard coating layer are formed in direct contact without including an additional layer. The hard coating film according to claim 10 , which is applied to a flexible display.
14. A window comprising a display glass and a hard coating film formed on the display glass, The hard coating film is the hard coating film according to claim 10.
15. An image display device comprising the window according to claim 14.
Citation Information
Patent Citations
Window and display device including the same
KR1020210150626A
Composition for hard coating and method of preparing the same and hard coating film produced by using the same
CN102482534A
Hard coat film and information display device
JP2016177163A
Composition for forming hard coat and optical film and image display device using the same
JP2016188996A
Multilayered film
KR1020150082124A